P784 A new questionnaire to investigate patients' knowledge of relevant aspects of inflammatory bowel disease clinical course and outcomes: preliminary results. (15th January 2020) - Zerboni, G; Barello, S; Festa, S; Aratari, A; Graffigna, G; Papi, C
Abstract: Background: Inflammatory bowel disease (IBD) patient's knowledge is a key factor for shared treatment decision making. Some studies have already investigated IBD knowledge but never focused on patient's awareness about the major disease outcomes nor clinical course nor therapeutic aspects. The aim of the present study is to assess disease knowledge in IBD patients using a novel 11 items questionnaire. Methods: An 11 items questionnaire was developed. The questionnaire explored different aspects of IBD course and prognosis: pattern of symptoms, disease complications, need for surgery, risk and prevention of colon-rectal cancer (CRC), extra-intestinal manifestations (EIMs), predictors of poor prognosis, benefit/risk of immunosuppressive and biological therapy and IBD in pregnancy. The questionnaire was handed out to consecutive Crohn's disease (CD) and ulcerative colitis (UC) patients in regular follow-up at a referral centre. Clinical and socio-demographic characteristics were collected in a dedicate database. Descriptive analysis of quantitative variables was presented as mean or median. Fisher test and Student's t-test were used for categorical and continuous variables. A p < 0.05 was considered statistically significant. Results: Three hundred and four patients were enrolled and 290 completed the questionnaire (95%). Of these 53% UC and 47% CD. The mean age was 51 years (range 18–83); 56% were male. Most of the patients were in clinical remission (85%). The mean number of appropriate answer was 4 upon 11. Overall only 26% answered successfully more than half of the items. Looking at the single items, two third of patients were aware of current strategies of CRC prevention, chance of EIMs and woman capability to become pregnant. The questions about immunosuppression and biologic therapy were more correctly answered by those patients who had experienced them ( p = 0.000001), whereas those about the risk of surgery were not influenced by the patient's previous clinical history (UC p = 1; CD p = 0.067). Only about one third of women were aware of the most relevant risk factor of worst pregnancy outcome. Age <40 years old ( p = 0.00003), high level of education (high school and degree, p = 0.0015) and current or previous biologic therapy ( p = 0.0007) were associated with a higher level of IBD knowledge. Conclusion: These results suggest that the overall disease knowledge in IBD patients is low and should be improved. Young age, education and biologic exposure are associated with an adequate awareness of disease course. This questionnaire should be validated and correlated to other patient-related measures such as health engagement and health literacy in prospective studies.